Development of an e-module based on virtual practicum integrated with local potential in invertebrate material - Herditiya Herditiya; Mustika Sari; Sri Koriaty (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Invertebrate learning is integrated with practicum activities, while the learning outcomes are directly identifying and analyzing the general characteristics of species. The electronic module (e-module) illustrates the innovative use of technology in education, which helps limited facilities and infrastructure, to carry out actual practicum in invertebrate learning activities. This study aims to determine the validity, practicality, and effectiveness of using e-modules based on virtual practicum on invertebrate material. This research method is Research and Development (RnD) adapted from Borg and Gall. The application used to develop e-modules is PubHTML5. This study produced an e-module practicum systematized invertebrate based on virtual practicum integrated with local potential, with a very valid level of validity, a practical result of 92.87%, and the effectiveness of the N-Gain value of 0.97 in the high category. So that the e-module based on virtual practicum integrated with local potential that is developed is feasible and practical to use in invertebrate practicum activities, and effectively improves student learning outcomes. With e-modules based on virtual practicum integrated with local potential, hampered laboratory activities can be carried out efficiently.Abstrak Pembelajaran avertebrata terintegrasi dengan kegiatan praktikum, adapun capaian pembelajarannya ialah mengidentifikasi dan menganalisis ciri-ciri umum spesies secara langsung. Modul elektronik (e-modul) merupakan gambaran pemanfaatan inovatif teknologi dibidang pendidikan yang membantu keterbatasan sarana dan prasarana, untuk melakukan praktikum riil pada kegiatan pembelajaran avertebrata. Penelitian ini bertujuan untuk mengetahui validitas, kepraktisan, dan keefektifan penggunaan e-modul berbasis virtual praktikum pada materi avertebrata. Metode penelitian ini adalah Research and Development (RnD) yang diadaptasi dari Borg dan Gall, Aplikasi yang digunakan untuk mengembangkan e-modul ialah PubHTML5. Penelitian ini menghasilkan e-modul praktikum sistematika avertebrata berbasis virtual praktikum terintegrasi potensi lokal, dengan tingkat kevalidan sangat valid, hasil kepraktisan sebesar 92,87%, dan kefektifan dari nilai N-Gain sebesar 0,97 dengan kategori tinggi. Sehingga e-modul berbasis virtual praktikum terintegrasi potensi lokal yang dikembangkan layak dan praktis digunakan dalam kegiatan praktikum avertebrata, serta efektif meningkatkan hasil belajar mahasiswa. Adanya e-modul berbasis virtual praktikum terintegrasi potensi lokal, kegiatan laboratorium yang terhambat dapat dilakasanakan dengan mudah.